Reconfigurable intelligent surface-aided joint radar and covert communications: fundamentals, optimization, and challenges - Du, Hongyang (2022)
Future wireless communication systems will evolve toward multifunctional integrated systems to improve spectrum utilization and reduce equipment sizes. Joint radar and communication (JRC) systems, which can support simultaneous information transmission and target detection, have been regarded as a promising solution for emerging applications, such as autonomous vehicles. In JRC, data security and privacy protection are critical issues. Thus, we apply covert communication to JRC and propose a joint radar and covert communication (JRCC) system to simultaneously achieve high spectrum utilization and secure data transmission. In the JRCC system, sensitive data transmission is hidden from malicious parties. However, the performance of JRCC is restricted by a severe signal propagation environment and hardware devices. Fortunately, reconfigurable intelligent surfaces (RISs) can intelligently change the signal propagation to improve network performance and cost. We first review fundamental concepts of JRCC and RISs and then propose a RIS-aided JRCC system design. Furthermore, covert communication and radar performance metrics are investigated, and a game theory-based covert rate optimization scheme is designed to achieve secure communication. Finally, we present several promising applications and future directions of RIS-aided JRCC systems.